Equivalência monetária em crianças surdas - MAGALHÃES, Priscila Giselli Silva (Universidade Federal do Pará, 2014)
In the teaching of monetary skills the procedures of matching to sample (MTS) and constructed response matching to sample (CRMTS) have proven effective. However, there is a controversy about the importance of prerequisites. Experiment 1 aimed to investigate the effect of teaching on the monetary equivalence in deaf children with different mathematical repertoires. A total of ten children participated. They were enrolled in a specialized school for deaf students, where the sessions were carried out and were distributed in two groups: Children with greater mathematical repertoire (Group I) and children with lower mathematical repertoire (Group II). A computer was used with software (REL 5.3.3 for Windows). Initially, the participants were exposed to pre-test and a pre-training identity. Then, the teaching of conditional relations in MTS between monetary value in Brazilian Signal Language (LIBRAS) and decimal numerals (AB), monetary value in LIBRAS and figures of coins (AC) and the monetary value in LIBRAS and figures of paper money (AD), followed by tests of symmetry and transitivity. In both groups, there was emergence of relations for most of the participants. Also a CRMTS teaching figures of paper money and decimal numerals (DB') was conducted, followed by tests of symmetry and transitivity. In the tests there was variability in responses in both groups. Post-tests and maintenance tests showed consistent performance with training. Experiment 2 aimed to replicate the results of experiment 1 verifying that changes in procedure would produce monetary equivalence in deaf children. Three deaf children participated. The experimental environment, materials and equipment were the same of Experiment 1. The procedure was similar to that used in Experiment 1, but with the introduction of some experimental phases: 1) randomized trials in the training, teaching numerical components and pre-training CRMTS. Results indicate the emergence of relations for the three participants in MTS and the emergence of a few relations in CRMTS. In both experiments the complexity of the task was one of the possible explanations of the performance and the prerequisites not interfered with the learning of this type of task.